Strengthening the Political Democracy of Regional Head Candidates through Independent Channels in Aceh - Dahlan A Rahman; M. Rizwan; Muchlis Muchlis (Budapest International Research and Critics University, 2022)
The significance of mapping the study of democratic parties through the presence of potential leaders as people's representatives in occupying executive positions in regional governments through individual channels. The unique path is a national legal political agreement in the area of elections that allows people who are not members of political parties to nominate themselves as regional heads in the Aceh region's provinces.The theory of political participation and leadership is used as a research mapping in an analytical scheme in this study. The research method employs a qualitative approach to interviewing techniques in order to examine the style of existence and political leadership of regional leaders on a case-by-case basis. The results explain: Individual candidates are more commonly referred to as